1996
DOI: 10.1152/ajplung.1996.271.1.l79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone on expression of adhesion molecules on CD4+ lymphocytes

Abstract: Despite the widespread use of corticosteroids in asthma therapy, little is known of the effects of corticosteroids on cell surface markers involved in T lymphocyte activation and adhesion. We used flow cytometry to analyze the effects of 1, 10, and 100 nM dexamethasone on expression of markers on resting and phytohemagglutinin (PHA)-stimulated peripheral blood CD4+ T lymphocytes. Expression of the leukocyte common antigen CD45 was significantly (P = 0.016, n = 3) increased from an average mean fluorescence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…However, this is not the case since the patients who were no longer able to walk had stopped steroid treatment before the analyses, and the changes in CD49d expression persisted. In addition, it has been reported that glucocorticoids do not modulate in vitro or in vivo CD49d expression [ 22 , 23 ]. Furthermore, all patients who were still able to walk were all under steroid treatment, thus excluding steroid treatment as a putative confounder.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not the case since the patients who were no longer able to walk had stopped steroid treatment before the analyses, and the changes in CD49d expression persisted. In addition, it has been reported that glucocorticoids do not modulate in vitro or in vivo CD49d expression [ 22 , 23 ]. Furthermore, all patients who were still able to walk were all under steroid treatment, thus excluding steroid treatment as a putative confounder.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, budesonide reduced surface ICAM‐1(CD54) upregulation induced by IFN‐γ. Hughes et al ( 22) found that dexamethasone had no effect on the expression of VLA‐4 (CD29) on peripheral blood CD4+ lymphocytes. Taken together, these studies suggest that the membrane expression of AM is differentially modulated by glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with a recent report by Hughes et al . [ 16], who reported no effects of dexamethasone on CD45RO expression in vitro .…”
Section: Discussionmentioning
confidence: 99%